The Relationship Between Social Support Levels and Anxiety in Saudi Women Facing Infertility - Dian Rahmatiya Adi Mula; Nila Widya Keswara (International Journal of Medicine and Health, 2025)
Infertility is a reproductive health issue that not only affects biological aspects, but also causes significant psychological burdens, particularly anxiety in women. In the context of Saudi Arabian culture, which has strong pronatalist values, infertile women often face social and emotional pressures that can exacerbate their psychological condition. Social support is seen as a protective factor that plays an important role in helping individuals adapt to the stress of infertility. This study aims to analyze the relationship between the level of social support and the level of anxiety in Saudi women facing infertility at the Dr. Sulaiman Al-Habib Takhassusi Branch, Riyadh. This study uses a quantitative approach with a cross-sectional analytical observational design. The research sample consisted of 30 infertile women selected using consecutive sampling techniques. The levels of social support and anxiety were measured using a standardized questionnaire, then analyzed using Spearman's correlation test with a significance level of 0.05. The results showed that most respondents were aged 20–35 years and experienced primary infertility. The Spearman test showed a statistically significant relationship between the level of social support and the level of anxiety (p = 0.000) with a correlation coefficient of r = 0.625, indicating a moderate to strong positive relationship. This indicates that women with higher levels of anxiety tend to receive or seek more intense social support. In conclusion, social support plays an important role in the dynamics of anxiety in infertile women. The integration of structured psychosocial support into infertility services is essential to improve patients' psychological well-being and quality of life.